Building Global Perspective with Interactive Media: A Case Study on Using Quizwhizzer and 3D Media at SDN Krejengan - Qomariyah , Ryzca Siti; Anjarwati , Ani; Ardiansari, Lia; Nisa, Adelia Khoirol (Journal of Education Method and Learning Strategy, 2025)
This research uses a descriptive qualitative approach and involves interviews with teachers as well as the implementation of materials through educational games and 3D media. The results show that although student engagement increased, there were challenges in understanding the material and using technology that affected students' quiz scores. This research aims to enhance students' understanding of global issues, particularly global warming. The results are expected to positively impact education and environmental awareness among the sixth-grade students of SDN Krejengan.